Polarization Responses of a Solitary and Optically Injected Vertical Cavity Spin Laser - Cemlyn, Benjamin R.; Henning, Ian D.; Adams, Michael J.; Harbord, Edmund; Oulton, Ruth; Korpijarvi, Ville-Markus; Guina, Mircea (IEEE journal of quantum electronics, 2019)
The polarisation properties of a quantum well spin - vertical cavity surface emitting laser (spin - VCSEL), both without injection and with variable polarisation optical injection, are investigated experimentally and compared with the spin flip model (SFM). Without injection, we demonstrate two distinct types of VCSEL-pump response depending on the signs of the linewidth enhancement factor, birefringence and dichroism: firstly where the pump and VCSEL have the same sign of the ellipticity, and secondly where the VCSEL ellipticity, accompanied by the linear polarisation, switches sign. We show that by controlling the injected power, ellipticity or linear angle, near circular polarisation can be obtained. These responses both give insight into the electro-optical injected spin-VCSEL system, and have practical implications for the use of spin VCSELs in unique applications exploiting the ellipticity degree of freedom.